The Role of Audio Visual Education in Contraceptive Use in 48-Hour Postpartum Women - Setiyorini, Luluk; Jayanti, Ratna Dwi; Utomo, Budi (Jurnal Kebidanan Midwiferia, 2025)
The 48-hour postpartum period is the ideal time to choose contraception because ovulation can occur 34 days postpartum for mothers who are not breastfeeding optimally. Audio-visual contraceptive education is provided during pregnancy to facilitate contraceptive use during the 48-hour postpartum period. This study aims to determine the relationship between knowledge levels after audio-visual education and contraceptive use during the 48-hour postpartum period. It also aims to identify contraceptive method use during the 48-hour postpartum period. This study is a pre-experimental study with a one-group post-test only design involving 30 pregnant women in the third trimester with a gestational age of ≥ 36 weeks, selected through consecutive sampling. The intervention was provided in the form of audio-visual education. Knowledge levels were measured using a questionnaire after the intervention. Postpartum contraceptive use was identified using medical records. The relationship between knowledge levels after the intervention and contraceptive use during the 48-hour postpartum period was measured using a chi-square test, yielding a p-value of 0.002, indicating a significant association between knowledge after the audio-visual education intervention and contraceptive use during the 48-hour postpartum perio. One of the key components of the Childbirth Planning and Complication Prevention Programme (P4K) is education about contraception during pregnancy. Family planning counselling and contraceptive methods during pregnancy can increase mothers' awareness of contraceptive use.